Inhibition of PAI-1 Activity by Toddalolactone as a Mechanism for Promoting Blood Circulation and Removing Stasis by Chinese Herb Zanthoxylum nitidum var. tomentosum - Yu, Bo; Zhang, Guangping; Jin, Lingling; Zhang, Bo; Yan, Dong; Yang, Hong; Ye, Zuguang; Ma, Tonghui (Frontiers in Pharmacology, 2017)
Traditional Chinese medicine has been used to treat a variety of human diseases for many centuries. Zanthoxylum nitidum var. tomentosum is used as an adjuvant to promote blood circulation and remove stasis. However, the mechanisms of improving circulation and other biological activities of Z. nitidum var. tomentosum are still unclear. Plasminogen activator inhibitor-1 (PAI-1) regulates the plasminogen activation system through inhibition of tissue-type and urokinase-type plasminogen activators (tPA and uPA). PAI-1 has been linked to fibrin deposition that evolves into organ fibrosis and atherosclerosis. In the present study, we showed that ethanol extract prepared from Z. nitidum var. tomentosum exhibited PAI-1 inhibitory activity, and identified toddalolactone as the main active component that inhibited the activity of recombinant human PAI-1 with IC50 value of 37.31±3.23 µM, as determined by chromogenic assay, and the effect was further confirmed by clot lysis assay. In vitro study showed that toddalolactone inhibited the binding between PAI-1 and uPA, and therefore prevented the formation of the PAI-1/uPA complex. Intraperitoneal injection of toddalolactone in mice significantly prolonged tail bleeding and reduced arterial thrombus weight in a FeCl3-induced thrombosis model. In addition, the hydroxyproline level in the plasma and the degree of liver fibrosis in mice were decreased after intraperitoneal injection of toddalolactone in CCl4-induced mouse liver fibrosis model. Taken together, PAI-1 inhibition exerted by toddalolactone may represent a novel molecular mechanism by which Z. nitidum var. tomentosum manifests its effect in the treatment of thrombosis and fibrosis.